Intensity of infection with intracellular Eimeria spp. and pinworms is reduced in hybrid mice compared to parental subspecies. (2nd January 2020) - Balard, Alice; Jarquín‐Díaz, Víctor Hugo; Jost, Jenny; Martincová, Iva; Ďureje, Ľudovít; Piálek, Jaroslav; Macholán, Miloš; Goüy de Bellocq, Joëlle; Baird, Stuart J. E.; Heitlinger, Emanuel
Abstract: Genetic diversity in animal immune systems is usually beneficial. In hybrid recombinants, this is less clear, as the immune system could also be impacted by genetic conflicts. In the European house mouse hybrid zone, the long‐standing impression that hybrid mice are more highly parasitized and less fit than parentals persists despite the findings of recent studies. Working across a novel transect, we assessed infections by intracellular protozoans, Eimeria spp., and infections by extracellular macroparasites, pinworms. For Eimeria, we found lower intensities in hybrid hosts than in parental mice but no evidence of lowered probability of infection or increased mortality in the centre of the hybrid zone. This means ecological factors are very unlikely to be responsible for the reduced load of infected hybrids. Focusing on parasite intensity (load in infected hosts), we also corroborated reduced pinworm loads reported for hybrid mice in previous studies. We conclude that intensity of diverse parasites, including the previously unstudied Eimeria, is reduced in hybrid mice compared to parental subspecies. We suggest caution in extrapolating this to differences in hybrid host fitness in the absence of, for example, evidence for a link between parasitemia and health. Abstract : The role of parasitism as main component of hybridization process in the European house mouse hybrid zone has been discussed for decades. Using an extracellular and an intracellular parasites, expected to trigger different immune pathways, in a large field sampling, we showed a similar pattern of decreased intensity = increased resistance of hybrids compared to parental mice.